2018
DOI: 10.6007/ijarbss/v8-i9/4689
|View full text |Cite
|
Sign up to set email alerts
|

Why Consumers are Hesitant to Shop Online: The Major Concerns towards Online Shopping

Abstract: Online purchases have become a new trend of shopping among university students in today's Industrial Revolution 4.0. But, not all university students are open to shop online. Therefore, this study aims to explore the major concerns towards online shopping that stops non-online shoppers to purchase online. The study aims to provide the needed information to understand the barriers for university students to shop online. A total number of 154 valid surveys were collected in local universities using convenience s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…Contrary to our finding, prior literature discovered a significant negative association between the tradition barrier and WOM (Kaur, Dhir, Ray, et al., 2020). The reason behind this finding might be that the use of online services has become highly matured, and consumers are not hesitating in using these services anymore (Aziz & Wahid, 2018). Hence, consumers are looking forward to recommendations related to innovative services offered on the online platform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to our finding, prior literature discovered a significant negative association between the tradition barrier and WOM (Kaur, Dhir, Ray, et al., 2020). The reason behind this finding might be that the use of online services has become highly matured, and consumers are not hesitating in using these services anymore (Aziz & Wahid, 2018). Hence, consumers are looking forward to recommendations related to innovative services offered on the online platform.…”
Section: Discussionmentioning
confidence: 99%
“…(Laukkanen, 2016). Prior studies have also recommended that image barrier is negatively associated with m‐commerce and electronic commerce (e‐commerce) purchase intention (Aziz & Wahid, 2018; Kleijnen et al., 2009; Moorthy et al., 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This study anticipates that if the family business can be passed on to the younger generation who are computer-savvy and ready to adopt technology in running the business, business will be able to last longer. Technological readiness has been widely used as a moderator in studies related to online purchasing behavior in the field of marketing where many studies have found that consumer readiness can strengthen the relationship between independent variables and online shopping behavior (Aziz & Wahid, 2018). However, studies that measure the effect of technology readiness in the entrepreneurship field such as family business is still lacking.…”
Section: Technology Readinessmentioning
confidence: 99%
“…Aktualizacija ove tematike po Norum (2008: 373-374) pridonosi otvaranju cijeloga istraživačkog područja u kojem je adresirana uloga mladih, napose studenata, kao nositelja suvremenih tehnoloških trendova koji čine lukrativno tržište dobara i usluga. Stoga ne čudi da su upravo oni učestalo ispitivana populacija na temu internetskog kupovanja u međunarodnoj literaturi (Lammers i dr., 2003;Dittmar, Long i Meek, 2004;Lester, Forman i Loyd, 2005;Park i Kim, 2007;Norum, 2008;Ciunova-Shuleska, Grishin i Palamidovska, 2011;Kiyici, 2012;Choudhury i Dey, 2014;Aziz i Wahid, 2018). Dijelom je to slučaj i u Hrvatskoj u kojoj se nekolicina znanstvenih radova, uglavnom iz područja ekonomije, bavi istraživanjem studentskih stavova i iskustava u internetskom kupovanju te problemima i prednostima u odnosu na klasične trgovine (Strugar, Knežević i Jaković, 2011); faktorima koji utječu na studentsku kupovinu s internetskih stranica za grupnu kupovinu (Bralić, Jadrić i Ćukušić, 2014); stavovima studenata o etičnosti prodaje online maloprodavača (Anić, Marković i Vouk, 2013); potrošačkim praksama mladih generacija u kontekstu kompulzivnosti, impulzivnosti i funkcionalnosti (Vojvodić i Matić, 2015); motivima kupovanja odjeće i kriterija odabira trgovina (Knežević, Delić i Ptić, 2016); korištenjem društvenih medija (Štulec, Petljak i Naletina, 2018).…”
Section: Uvodunclassified